Instrumental strategies and symbolic legitimacy: analyzing government information disclosure security policies in China - Ling Chen; Lianjian Deng (PLoS ONE, 2025)
This study explores how the Chinese government manages the trade-off between transparency and national security through the design of government information disclosure (GID) security policies. Based on a qualitative analysis of 259 policy documents issued at central, provincial, and prefectural levels between 2007 and 2024, we construct a two-dimensional framework that integrates policy instrument types (supply, environmental, demand) with policy content stages (readiness, implementation, impact). The findings reveal an overreliance on environmental-type instruments—especially during implementation—and underuse of demand-oriented tools that support public participation and accountability. Through the lens of Governmental Power Marketing (GPM), we interpret this instrument selection not only as a technical response but as a symbolic strategy to project institutional competence and legitimacy. This study contributes to digital governance literature by linking content analysis with political communication theory, offering both an analytical framework and comparative insights applicable to other regimes facing similar transparency-security dilemmas.